BOOK REVIEWS (Journal of Finance, 1956)
Book reviewed in this article: Business Finance: Corporate Financial Policy . By H arry G. G uthmann and H erbert E. D ougall . Financing Business Firms . By C harles L. P rather . Insurance: Its Theory and Practice in the United States . By A lbert H. M owbray and R alph H. B lanchard . International Finance: Introduction to International Trade and Finance . By L orie T arshis . Foreign Capital in Latin America . By U nited N ations D epartment of E conomic and S ocial A ffairs . Investments: Cases and Problems in Investments . By F rancis J. C alkins . The Art of Investment . By A. G. E llinger . How to Invest Your Money . By R alph C. E pstein . Money and Banking: The Great Inflation 1939–1951 . By A. J. B rown . Short‐Term Economic Forecasting . By the C onference on R esearch in I ncome and W ealth . The Great Crash 1929 . By J ohn K enneth G albraith . Public Finance: Federalism, Finance and Social Legislation in Canada, Australia, and the United States . By A. H. B irch . The Redistribution of Income in Postwar Britain: A Study of the Effects of the Central Government Fiscal Program in 1948–49 . By A llan M urray C artter . Financing Metropolitan Government . Edited by C arl H. C hatters . Essays in Public Finance and Fiscal Policy . By G erhard C olm . The Federal Tax System of the United States: A Survey of Law and Administration . By J oseph P. C rockett . Principles of Public Finance . By H ugh D alton . Financing Municipal Government in Denver . By E. T. H alaas . Soviet Taxation: The Fiscal and Monetary Problems of a Planned Economy . By F ranklyn D. H olzman . The Ownership of Tax‐Exempt Securities, 1913–1953 . By G eorge E. L ent . Pensions in Our Economy . By S tephen R aushenbush . Readings in Fiscal Policy . Edited by A rthur S mithies and J. K eith B utters . Taxes and Fiscal Policy in Under‐developed Countries . By U nited N ations T echnical A ssistance A dministration .